Intellectual Disability, Art and Identity: A qualitative exploration of the experiences of professional artists with intellectual disabilities - Garcia Iriarte, Edurne (My University, 2022)
Previous research suggests that participation in the arts and/or disability arts can positively influence individuals’ affirmation, or a positive embracement, of a disability identity; however, until more recently, persons with intellectual disabilities have not been included in this research to the same extent as their peers with physical or sensory disabilities. This article contributes to the increasing empirical consideration of intellectual disability identity among professional artists. Data were collected via two focus groups, one with five performing artists and the second with five visual artists, as well as follow-up, individual interviews with 8 of the artists. Key findings were identified via thematic analysis. Findings show affirmation of an intellectual disability identity emerged as a stronger theme among performing artists than visual artists. Additional themes related to confidence development, peer relationships and demonstrations of capability supported the notion that professional art practice can foster the affirmation of an intellectual disability identity.
PUBLISHED
Keywords: Disability identity; Identity; Affirmative model; Disability art; Art; Intellectual disability; Inclusive Society; ART; IDENTITY; INTELLECTUAL DISABILITY; Inclusive research; QUALITATIVE RESEARCH